Synthesis and Characterization of Copper Nanoparticles/Polyvinyl Chloride (Cu NPs/PVC) Nanocomposites. (2015) - Guzman, A.; Arroyo, J.; Verde, L.; Rengifo, J.
Abstract: In the present work, two-synthesis method for copper nanoparticles (Cu NPs) in polyvinyl chloride polymer (PVC) has been developed by adding previously synthesized NPs to the resin and by an in situ synthesis of the NPs. The resin was mixed with additives to enhance obtaining a pasty mixture called plastisol. The obtained plastisol is liquid at room temperature and have viscoelastic and pseudoplastic properties. The plastisol showed changes in its mechanical properties by heat action, like a remarkable increase of viscosity at high temperatures, passing from the initial liquid state to solid state at curing temperature (180-200 °C). Cu NPs were synthesized previosusly by microwave assisted polyol method, using copper acetate (CuAc2) as precursor, ascorbic acid (AA) as reducing agent, polivinilpirrolidone (PVP) as stabilizer and ethylene glycol as solvent. In this synthesis ethylene glycol (EG), a diol widely used in polyol method; was used as a solvent. Microwaves provided thermal heating, an alternative to the conventional heating by convection. The microwave irradiation was successfully used to warm dielectric materials, considering the property of tangent loss (tan δ), the higher the value, the greater transformation of electromagnetic microwave energy into heat energy was achieved, this one occurs preferably in polyol, such as ethylene, which has high dielectric constant. Different concentrations of plasticizer and several temperatures were evaluated for curing nanocomposites (Cu NPs/PVC). To obtain films of Cu NPs/PVC, a coating technique over a substrate (paper or fabric transfer) was used. Films were prepared in order to produce a material with further bactericidal activity. The characterization was performed by X-Ray diffraction and ultraviolet visible spectrophotometry.